Coerência e princípios jurídicos: uma leitura (moral) de Ronald Dworkin - Matos, Daniel Ortiz (Universidade do Vale do Rio dos Sinos, 2014)
This master's thesis is a (moral) reading of the theoretical conception of Ronald Dworkin about the legal principles. The main point is to understand the role of the principles in dworkinian theory of judicial decision trying to reveal its underlying justification model. This thesis is subdivided into three parts. In the first one, addressed for the famous Hart-Dworkin debate, the goal is to try to understand whence came the emphasis on principles, not as a repetition of the argumentative struggle, but, above all, demonstrating the theoretical and philosophical limitations of the hartian project and how the principles evidence them. In the second part, it is developed an overview of the legal set of principles in Dworkin, relating to the key concepts of his theory, such as: the critique of the judicial discretion; the thesis of the rights; the thesis of (only one) correct answer; the commonality of principles and the "Law as Integrity" conception. In the third and last part, the discussion will turn to Coherentism, specifically to the procedure of Rawls' reflective equilibrium and its incorporation in Dworkin's adjudication theory, and, therefore, indispensable to the role of the principles for the legal system coherence and to the verifiability of the correction of judicial responses.
Keywords: Ronald Dworkin; John Rawls; Princípios jurídicos; Equilíbrio reflexive; Coerência; Legal principles; Reflective equilibrium; Coherence; ACCNPQ::Ciências Sociais Aplicadas::Direito